METHODOLOGICAL STRATEGY TO ACHIEVE DEVELOPING EVALUATION IN MATHEMATICS AT THE KUANDO KUBANGO, ANGOLA TEACHER TRAINING SCHOOL - Miguel Kanhime Kasabube; Walfredo González Hernández (Universidad Distrital Francisco José de Caldas, 2017)
In this paper we did an analysis of theoretical foundations in order to study essential characteristics of developing evaluation in Mathematics teachers education. From our perspective it is essential to analyse evaluation as a process integrating aspects from a variety of disciplines like psychology, philosophy, didactics and mathematics. Thus, is very important to clarify this didactic category designed specially to develop evaluation processes in Angola's environment. In the proposal development was used predominantly a qualitative paradigm, based on data obtained through several empirical methods. We present the strategy to achieve this evaluation process on the socio- historical context, promptly related with professional's training. Finally, we present results of testing this strategy.